IMPLEMENTASI MULTI AKAD DALAM LAYANAN PEMBIAYAAN GADAI SYARIAH DI BANK BTN SYARIAH KC SOLO - Djayusman, Royyan Ramdhani; Damanhuri, Sahnaz Emira Damanhuri Emira (HUMAN FALAH: Jurnal Ekonomi dan Bisnis Islam, 2025)
The sharia pawn financing service has become one of the financingsolutions favored by many people, including at Bank BTN Syariah KC Solo. Thecontract used is a combination of rahn, qardh, and ijarah aimed at meeting shortterm financing needs in accordance with sharia principles. The purpose of thisresearch is to analyze the mechanism of implementing rahn, qardh, and ijarahcontracts at Bank BTN Syariah KC Solo from the perspective of Islamic economiclaw. This research uses a descriptive qualitative method with a case studyapproach. Data were collected through in-depth interviews with bankrepresentatives and Sharia experts, as well as direct observations. The researchresults show that the implementation of ijarah, qardh, and rahn contracts in thesharia pawn financing services at Bank BTN Syariah KC Solo is in accordancewith sharia principles. The rahn and ijarah contracts are conducted separately,where the rahn contract provides security in transactions through the loan ofgoods (marhun), while the ijarah contract is used to charge fees for the storage ofpawned goods without any additional elements of usury. It is hoped that BankBTN Syariah KC Solo can enhance transparency and sharia literacy in thecommunity to strengthen customer trust.